Physiotherapy treatment for pain reduction and improvement of function in jumping athletes with patellar tendinopathy: literature review (Research, Society and Development, 2022)
Therapeutic exercises are widely used in the rehabilitation process of patellar tendinopathy (PT). However, there are divergences in the literature related to the intensity and/or frequency of these exercises. The aim of this study is to update and identify what would be the best kinesiotherapeutic intervention for the treatment of patellar tendinopathy (PT) to reduce pain and improve function in jumping athletes. The research is characterized as a literature review, following the PRISMA guidelines. The research was performed in the Pubmed and PEDro databases, articles published between the years 2005 and 2021, following the descriptors "Patellar tendinopathy" OR "jumper's knee AND treatment OR exercise therapy AND conservative treatment AND rehabilitation". The inclusion criteria were articles in English and randomized clinical trials. Studies in other samples, as well as articles that did not address the topic, were excluded. 221 studies were identified for this review, nine of which were selected for analysis and development. Therapeutic exercise through quadriceps muscle strengthening, regardless of type, was effective in reducing pain and improving function in athletes with PT. Among the forms of conservative treatment for PT, muscle strengthening is the most effective, safe, and long-lasting. However, regarding dose and intensity, the findings of this review are conflicting.